Larval development of Libinia rhomboidea Streets, 1870 (Crustacea: Decapoda: Brachyura: Majoidea) under laboratory conditions - Cházaro-Olvera,Sergio (2020)
Abstract In this study, the larval development of Libinia rhomboidea Streets, 1870 under laboratory conditions is described and compared with the description of Libinia spinosa H. Milne Edwards in Guérin, 1832, Libinia dubia H. Milne Edwards, 1834, and Libinia emarginata Leach, 1815 published by other authors. The ovigerous females collected released larvae asynchronously. Two zoeas and one megalopa stage were obtained. Larval development required 13 to 14 days at 20.5 - 22.0°C and 32 - 35 psu of salinity. The differences in L. rhomboidea with respect to the other three species are the following: in the first zoea, the total length and carapace length were greater and the number of setae on the basial endite of the maxillula was different; in the second zoea the size of the endopod and the number of setae on the scaphognathite of the maxilla were greater; in the megalopa, the total length and carapace length were both greater, while the number of setae on the scaphognathite of the maxilla was less. A great similarity between L. rhomboidea and L. dubia was found; however, it is possible to distinguish the larval morphology of L. rhomboidea from the three species compared.